Self-regulation, strategies and self-motivation in the learning process - Herczeg, Claudia; Lapegna, Mónica (Lenguas Modernas, 2010)
Self-regulation, defined as the conscious process of observation and control of our own thinking processes, determines to a large extent whether a specific learning task is successful or not. A major aspect in self-regulated earning is the ability to develop and apply suitable strategies for each specific learning purpose. This, in turn, is directly influenced by motivational factors. The aim of this paper is to examine the theoretical concepts that underlying self-regulation, strategies and motivation so as to describe how they are interrelated and in what ways they influence the learning process.